Launch seminar on the new engineering contract 2nd edition delegate information : 3 October 1995, London Metropole. (Thomas Telford, 1995)
This title is part of the ICE Publishing complete digital collection - helping ensure access to essential engineering content from past to present. Proceedings of a launch seminar held at London Metropole in 1995.